A-site deficient chromite perovskite with in situ exsolution of nano-Fe: a promising bi-functional catalyst bridging the growth of CNTs and SOFCs. Issue 28 (28th July 2015) - Sun, Yi-Fei; Li, Jian-Hui; Wang, Meng-Ni; Hua, Bin; Li, Jian; Luo, Jing-Li
<x xml:space="preserve">Abstract</x> A bi-functional Fe-doped chromite perovskite with A-site deficiency facilitates the in situ exsolution of Fe nanoparticles. The material provides high-density reaction sites for fuel oxidation in SOFCs and growth of carbon nanotubes which further enhances the electrochemical performance of SOFCs.